METHODS OF ENCRYPTION BASED ON PERMUTATION UNITS WITH VARIABLE LENGTH - Лужецький, Володимир Андрійович; Горбенко, Іван Сергійович (Ukrainian Information Security Research Journal, 2015)
One of the main operations performed by the block ciphersregardless to their architecture is permutation.Modern block ciphers perform permutation operationonly inside a separate block or small group of blocks. Inone of the previous articles the method of pseudorandompermutation of blocks inside the entire message was offeredbut modern block ciphers have fixed block lengthso even after permutation the beginning and endingblocks positions remain known. To increase the cryptographicstrength fragmentation the message to variablelength blocks is offered. Ciphering methods based onvariable length blocks permutation were developed, recommendationsconcerning blocks length quantity andtheir range were produced, the rules of pseudorandomblocks length values generating were offered and compared from cryptographic strength providing point ofview.